Altered gut microbiota and short chain fatty acids in Chinese children with autism spectrum disorder - Liu, Simeng; Li, Enyao; Sun, Zhenyu; Fu, Dongjun; Duan, Guiqin; Jiang, Miaomiao; Yu, Yong; Mei, Lu; Yang, Pingchang; Tang, Youcai; Zheng, Pengyuan (Scientific reports, 2019)
Autism spectrum disorder (ASD) is a neurodevelopmental disorder that is characterized by impairments in social interactions and communication, restricted interests and repetitive behaviors. Several studies report a high prevalence of gastrointestinal (GI) symptoms in autistic individuals. Cumulative evidence reveals that the gut microbiota and its metabolites (especially short-chain fatty acids, SCFAs) play an important role in GI disorders and the pathogenesis of ASD. However, the composition of the gut microbiota and its association with fecal SCFAs and GI symptoms of autistic children remain largely unknown. In the present study, we sequenced the bacterial 16S rRNA gene, detected fecal SCFAs, assessed GI symptoms and analyzed the relationship between the gut microbiome and fecal SCFAs in autistic and neurotypical individuals. The results showed that the compositions of the gut microbiota and SCFAs were altered in ASD individuals. We found lower levels of fecal acetic acid and butyrate and a higher level of fecal valeric acid in ASD subjects. We identified decreased abundances of key butyrate-producing taxa ( Ruminococcaceae, Eubacterium, Lachnospiraceae and Erysipelotrichaceae ) and an increased abundance of valeric acid associated bacteria ( Acidobacteria ) among autistic individuals. Constipation was the only GI disorder in ASD children in the present study. We also found enriched Fusobacterium , Barnesiella, Coprobacter and valeric acid-associated bacteria ( Actinomycetaceae ) and reduced butyrate-producing taxa in constipated autistic subjects. It is suggested that the gut microbiota contributes to fecal SCFAs and constipation in autism. Modulating the gut microbiota, especially butyrate-producing bacteria, could be a promising strategy in the search for alternatives for the treatment of autism spectrum disorder.